A MODEL OF GREEN RESIDENTIAL BUILDINGS AMONG HOMEBUYERS : A CASE STUDY OF RESIDENTIAL BUILDING - Afzan, Ahmad Zaini; Nur Khairina, Khairul Hisham; Anny Tang, Jia Siew; Nurul Nadia, Abdul Aziz; John, Tookey (School of Engineering, Taylor’s University, 2025)
Green housing (GH) is considered a dominant approach to achieve sustainable urbanisation in both developed and developing nations such as Malaysia. However, the supply of green-certified residential buildings in Malaysia remains limited than conventional housing. This is exemplified by the inexistence of GH projects within the largest state in Malaysia, namely Sarawak. All these circumstances motivate the present research to explore the implementation of a model of green residential buildings among homebuyers in Sarawak. A questionnaire survey was used to collect data from 200 respondents, and the Statistical Package for the Social Sciences (SPSS) software was employed for data analysis purposes. Overall, homebuyers’ value perception and trustworthiness had the most significant influence on their purchase intention. The Model of Green Residential Buildings offers valuable insights into potential homebuyers' awareness and readiness to embrace the green concept for their future homes. Additionally, it assists developers, the government, and policymakers in understanding homebuyers’ intentions and expectations regarding green housing (GH), enabling them to formulate effective development and marketing strategies to drive the expansion of GH projects in Sarawak.